2018
DOI: 10.18683/germs.2018.1141
|View full text |Cite
|
Sign up to set email alerts
|

Hypervirulent Klebsiella pneumoniae as a hospital-acquired pathogen in the intensive care unit in Mansoura, Egypt

Abstract: Introduction Hypervirulent Klebsiella pneumoniae (hvKP) are variants of K. pneumoniae that come up worldwide. hvKP is known in community-acquired infections but little is known about its role in hospital-acquired (HA) infections. The aim of this study was to evaluate the frequency of hvKP among HA K. pneumoniae infections in the intensive care unit (ICU) and to compare virulence and antibiotic susceptibility between hvKP and classical K. pneumoniae (cKP). Methods String test, biofilm formation, serum bacterici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
20
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 28 publications
6
20
3
Order By: Relevance
“…Formation of biofilm provides superior protection for Kp species against the host immune responses, the action of antibiotics and enhances its persistence [35].According to current results about 91.2% and 100% of cKp and hmvKp isolates were respectively potential biofilm producers but with no statistically significant difference. This finding was similar to the previous studies of El-Mahdy et al [37], Yan et al [27] and Cubero et al [24]. On the other hand, Fu et al [39] and Wu et al [40]documented that biofilm production was higher in hmvKp than cKp with a statistically significant difference.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…Formation of biofilm provides superior protection for Kp species against the host immune responses, the action of antibiotics and enhances its persistence [35].According to current results about 91.2% and 100% of cKp and hmvKp isolates were respectively potential biofilm producers but with no statistically significant difference. This finding was similar to the previous studies of El-Mahdy et al [37], Yan et al [27] and Cubero et al [24]. On the other hand, Fu et al [39] and Wu et al [40]documented that biofilm production was higher in hmvKp than cKp with a statistically significant difference.…”
Section: Resultssupporting
confidence: 91%
“…In our study, 26.3% and 7.4% of cKp and hmvKp isolates were respectively AmpC producers with a statistically significant difference (p<0.05), a finding that matched with results of Abd-Elmonsef et al [36]. Higher rates were showed by El-Mahdy et al [37] in Egypt who reported 50% of hmvKp and 55.7% cKp isolates as AmpC positive isolates.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…The study found that 37.8% (87/230) isolates were hvKp, and the prevalence of hvKp varied among different cities, with the highest rate in Wuhan (73.9%) and the lowest in Zhejiang (8.3%) [18]. Based on being positive for either iucA, or iroB gene, a total of 65 K. pneumoniae isolated from 65 patients with hospital-acquired infections in the ICUs of Mansoura University Hospital in Egypt were subjected to hvKp identification, of which only four strains were identified as probable hvKp [19]. With magA and rmpA genes being amplified by end point PCR, only three (7.9 %) out of 38 K. pneumoniae isolates carried one or both hvKp-associated genes in Houston, TX, USA [20].…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, the hvKp proportion of our study was significantly higher than those of foreign reports. Based on being positive for either iucA, or iroB gene, a total of 65 K. pneumoniae isolated from 65 patients with hospitalacquired infections in the ICUs of Mansoura University Hospital in Egypt were subjected to hvKp identification, of which only four strains were identified as probable hvKp[20]. With magA and rmpA…”
mentioning
confidence: 99%